The Role of Information Accuracy and Outcome Transparency on Forced Distribution Rating System (FDRS) Bias: An Experimental Study - Fuadhillah Kirana Putri (Future Science, 2020)
Forced Distribution Rating System (FDRS) is a performance appraisal system that forces supervisors to distribute employee rating results according to predetermined categories. FDRS aims to distinguish high, average, and low-performing employees so that low-performing employees can be identified. In practice, the supervisor experiences problems in assessing low-performing employees because the supervisor often does not have any data about these employees, so that bias cannot be avoided. By using the Equity Theory and Social Comparison Theory, this study aims to test empirically the role of information accuracy and outcome transparency as control systems in minimizing bias in FDRS. This study used a web-based experimental method with a 2x2 design between subjects with two information accuracy treatments (high and low) and two outcome transparency treatments (high and low). The results showed that high information accuracy affects the supervisor's intentions to avoid bias in FDRS. The results also indicate that the high outcome transparency strengthens the supervisor's intentions to avoid bias in FDRS when the information accuracy is relatively high. The highest tendency for a supervisor to do bias in FDRS is in a condition when there is low information accuracy with a high level of outcome transparency